Evaluating the effects of oral contraceptive use on biomarkers and body composition during a competitive season in collegiate female soccer players - Bozzini, B. N.; McFadden, B. A.; Elliott-Sale, K. J.; Swinton, P. A.; Arent, S. M. (Journal of Applied Physiology, 2021)
High training demands throughout the competitive season in female collegiate soccer players have been shown to induce changes in biomarkers indicative of stress, inflammation, and reproduction, which may be exacerbated in athletes using oral contraceptives (OCs). This study aimed to compare biomarkers and body composition between OC-using and nonusing (CON) female soccer players throughout a competitive season. Female collegiate soccer players were stratified into two groups based on their reported OC use at the start of preseason (OC: n = 6; CON: n = 17). Before the start of preseason and immediately postseason, athletes underwent a battery of performance tests. Blood draws and body composition assessments were performed before preseason, on wks 2, 4, 8, and 12 of the season, and postseason. Area-under-the-curve ratios (OCAUC:CONAUC) indicated the OC group were exposed to substantially higher levels of sex hormone-binding globulin (AUCratio = 1.4, probability = P > 0.999), total cortisol (1.7; P > 0.999), C-reactive protein (5.2; P > 0.999), leptin (1.4; P = 0.990), growth hormone (1.5; P = 0.97), but substantively lower amounts of estradiol (0.36; P < 0.001), progesterone (0.48; P = 0.008), free testosterone (0.58; P < 0.001), follicle-stimulating hormone (0.67; P < 0.001), and creatine kinase (0.33, P < 0.001) compared with the CON across the season. Both groups increased fat free mass over the season, but CON experienced a greater magnitude of increase along with decreased body fat percentage. Although similar training loads were observed between groups over the season, the elevated exposure to stress, inflammatory, and metabolic biomarkers over the competitive season in OC users may have implications on body composition, training adaptations, and recovery in female athletes.